Relative fitness of s-triazine susceptible and resistant biotypes of Chenopodium album - Leroux, G.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
The relative fitness of s-triazine susceptible and resistant biotypes ofChenopodium album from Quebec were compared in three greenhouse experiments. Under non-competitive conditions, there was no difference in dry matter production between biotypes, but the resistant biotype allocated less dry matter to seed production and produced fewer seeds than the susceptible. Results from de Wit replacement series performed at 400 plants m2 indicated that the relative proportion of biomass and seeds produced by the susceptible biotype was always greater than the proportion of susceptible plants present in any given treatment. The effects of root, shoot, and full (root + shoot) competition were compared between and within biotypes at planting densities of 400,666,934,1200, and 1466 seedlings m-2. Biotype had the most pronounced effect on all variables among the factors studied. The susceptible seedlings were taller, had a greater leaf area index (LAI), more leaves, and greater leaf, stem, and above-ground dry matter yields than the resistant seedlings, regardless of the planting density or the mode of competition. The fitness of the susceptible biotype was greatest when both biotypes were competing for light. The effects of shoot competition for light on yield, LAI, leaf numbers, and seedling height, were as important as those of full competition. The effects of root competition, although significant, were not nearly as important. The data indicate that if s-triazines are no longer used in a field, the C. album population will revert naturally to susceptibility because of the superior fitness of the susceptible biotype.